Technology Effect of EFL Listening Comprehension to Teacher during Pandemic - Sunjayanto Masykuri, Edi (Journal of English Teaching and Learning Issues, 2022)
The purpose of this research is to determine the impact of technology to student who taught listening comprehension during pandemic. The researchers recruited 66 senior high school students for this study. A test was used as a research instrument by the researchers. To display the material, the researchers used Learning Management System and Short Video on YouTube. The data was analyzed statistically by the researchers using an Anates program. The findings of this study indicate that technology-assisted language learning has a significant effect on EFL Listening Comprehension. This discovery demonstrated that technology-assisted language learning is an effective strategy for teaching Listening comprehension.